The national youth team program in Finland - Haemaelaeinen, J. (The Coach, 1997)
Ten years ago a sports school system was founded in Finland. We noticed that this would be our chance to build up a training center for volleyball too. We centered it in Trampere, the second biggest Finnish town. In Trampere one Sports Institute (Varala) and two active Sports Schools (Sampo High School and Pirkanmaa Vocational School) already were working, they were very interested in our idea. Our plan was to get the most talented players of every age together in the Training Center. We tried to establish the most professional training conditions here. The living circumstances and regular school work have been arranged in cooperation with the Sports Institute (where the Training Center is) and the sport schools. The Volleyball Training Center started with boys in 1987, with girls it started in 1991.